Characterization of Yellow Tabebuia Flower Extract (Tabebuia aurea) Nanoparticles and Bioactivity as Antioxidant: Karakterisasi Nanopartikel Ekstrak Bunga Tabebuya Kuning (Tabebuia aurea) dan Bioaktivitas sebagai Antioksidan - Yunita, Yunita; Syarifah, Anisa Lailatusy; Rahayu, Lina Oktavia; Wijayanti, Ernanin Dyah (Universitas Tidar, 2025)
Degenerative diseases can be prevented by natural antioxidants in plant. Yellow tabebuia flower is natural antioxidants. Plant extracts can develope into green synthesis nanoparticle to increase the effectiveness as medicinal materials. This research aims to determine the characteristics of yellow tabebuia flower extract nanoparticles and bioactivity as antioxidants. The methods included preparation and extraction of simplisia using ethanol solvent by maceration and sonication. The extract was determined flavonoid and phenol content by colorimetric method and antioxidant activity by DPPH method. The extract was also made into nano particles by ionic gelation method, with variations addition of tween 80 as much as 0.5, 0.75 and 1 ml. The results of this research are extract has a yield 13.09%, contains flavonoids, tannins, phenolics, alkaloids, saponins and terpenoids. The value of total flavonoid content is 0.59%, total phenolic content is 3.11% and antioxidant activity test has IC50 value of 165.26. The use ionic gelation method can reduce particle size. Three formulas that made the variation surfactant addition has a particle size of 47-283 nm, in addition tween80 1 ml has the smallest particle size of 47 nm with a zeta potential value of 39.3 mV. Keywords: yellow tabebuia flower extract, nanoparticles, antioxidant activity